EVALUATION OF ANTIMICROBIAL EFFICIENCY AND Î‘LPHA-GLUCOSIDASE INHIBITION OF RUBUS ELLIPTICUS SMITH. LEAF EXTRACTS AND ITS PHYTOCHEMICAL ANALYSIS - Latha R,; Sarkar, Trayee; Jansi R, Sagaya; p, Agastian (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The aim of this study was to investigate phytochemicals, antimicrobial and Î±-glucosidase inhibition effects of Rubus ellipticus. Methods: Various solvent extracts were investigated for its phytochemical analysis. Total phenol content (TPC) and total flavonoid content (TFC) were determined by using standard methods. The extracts of R. ellipticus were tested for antimicrobial activity and in vitro Î±-glucosidase inhibition effect. Results: The phytochemical tests revealed the presence of phytocontituents significantly in methanol extract with high TPC and TFC. Methanol extract showed significant antibacterial activity against Gram-positive and negative strains, as well as a strong antifungal activity. The maximum inhibition zone is found against Staphylococcus aureus, Micrococcus luteus and methicillin-resistant S. aureus (MRSA) (22, 17 and 18 mm) respectively. Against fungus the inhibition zone ranged between 19 mm and 23 mm. Methanolic extract showed minimum inhibitory concentration value with 32.5 Î¼g/ml against S. aureus, 62.55 Î¼g/ml against MRSA, Aspergillus flavus, Trichophyton mentagrophytes, Trichophyton rubrum 15 Î¼g/ml against Aspergillus niger. The methanol extracts and standard acarobose showed significant Î±-glucosidase inhibition effect with 86.14% and 92.46%. Conclusions: Correlation achieved by antimicrobial activity and Î±-glucosidase inhibition of R. ellipticus and its chemical composition insinuates that the activities may be easily ascribed to phenolic compound and flavonoids present in the high percentage in the leaf. Thus, our findings could provide a basis of future studies on R. ellipticus leaves used in food and pharmaceutical applications. Keywords: Rubus ellipticus, Phytochemical, Phenolic and flavonoid content, antimicrobial activity, Î±-glucosidase inhibition.